Mls-1 is encoded by the long terminal repeat open reading frame of the mouse mammary tumor provirus Mtv-7. - Beutner, U (1992)
The murine Mls-1 antigen is the prototype of endogenous superantigens, molecules whose activities lead to deletion of T cells expressing certain T-cell receptor V beta genes from the mature repertoire. However, Mls-1 also stimulates T cells expressing these particular V beta genes (V beta 6, V beta 7, V beta 8.1, and V beta 9) in vitro, making it one of the strongest known T-cell activators. We have recently reported that the Mls-1 gene is closely linked to the endogenous mammary tumor virus Mtv-7. We now demonstrate that Mls-1 is encoded by the open reading frame in the U3 region of the long terminal repeat of Mtv-7. However, control of expression of this molecule seems complex, depending on the promoter used for the transfection experiments. The sequence of the Mtv-7 open reading frame differs from all other known mammary tumor virus open reading frame sequences in the 3' end, suggesting that the T-cell receptor V beta specificity is conferred by the C terminus of the molecule. The predicted structure of the protein encoded by the open reading frame is consistent with a type II transmembrane molecule where the C terminus is extracellular.